ANALISIS PERLAKUAN AKUNTANSI TERHADAP PERKEBUNAN (TANAMAN) KARET (Studi Kasus Pada Pt. Perkebunan Nusantara Vii (Persero) Unit Usaha Way Berulu Kabupaten Pesawaran) - Uli Pangestu, Esti Fitra (Jurnal Manajemen dan Keuangan, 2010)
This research was conducted in order to determine the accounting treatment applied by PT. Perkebunan Nusantara VII (Persero) business unit berulu way in determaining the cost of immature and mature when compared with the accounting treatment according to the accounting concepts and also to determine what costs that could be capitalized cost of immature and mature, which is presented in the financial statements.Analysis tool used was a qualitative analysis to explain and illustrate the characteristics of the data so that research results can provide a clear picture. Analyzing qulitative analysis of data by using a theoretical approach related to the accounting treatment for immature and mature plants in pricing in determaining. Data used only the period from 2005 until 2007, so it is more clear in the submission by comparing the financial accounting standards with the accounting policy of the respective companies.In this study we concluded that the accounting policies applied by the company PT. Perkebunan Nusantara VII (Persero) business units berulu way consistent with financial accounting standards. In determining the acquisitions of plant, the costs of out is the result of the capitalization of costs incurred on inputs in the immature group. In determining the acquisitions price becomes the basis of plant yield at-5year-old rubber trees and is the present value of depreciation in the financial statements of the company.Keyword : immature and mature